DRUM LEARNING AND MOTOR SKILLS: EXPLORING TEACHER MOTIVATION AND DIRECT STRATEGIES IN PRIVATE LESSONS - Sembiring, Piter (Universitas Tanjungpura, 2025)
This study explores the integration of teacher motivation and direct instructional strategies in the development of students